Tingkat Kepuasan Pengguna E-Learning Mahasiswa Pascasarjana Universitas Swasta Terbaik di Jakarta: Pembelajaran Online Learning Pascasarjana Selama Pandemi Covid-19 pada Tahun 2020-2021 - Ayub Ezra R; Astari Retnowardhani (ITEJ (Information Technology Engineering Journals), 2022)
Innovation learning that is relatively cheaper, easily accessible, or an integrated system as an e-learning platform in blended or hybrid. The purpose of this study was to analyze the effect of using e-learning on the satisfaction level of postgraduate students at a private university in Jakarta during the COVID-19 pandemic. Sample data obtained from postgraduate students; the number is 324 postgraduate students through online questionnaires on a google form. To conduct research testing through PLS-SEM analysis with the help of the SmartPls application version 3.0. The results of this study indicate that for H1 the original sample value is 0.158, the p-value is below 0.05, and the t-statistic is 2.791, which is greater than the t-table value of 1.962. For the results of H2, the original sample value is 0.132 and the p-value is above 0.05, and the t-statistic is 1.583 which is smaller than the t-table value of 1.962. For the H3 results, the original sample value is 0.201, the p-value is below 0.05, and the t-statistic is 2.221 which is greater than the t-table value of 1.962. So that, the overall result of this research is that the quality of the system, and the quality of information that affect the level of user satisfaction.